The Outcome of 428 Cases of Scorpion Sting Syndrome in Atbara Locality, North Sudan - Elmadhoun, Wadie Mohamed Yasin; Mukhtar, Elham Nasr Edin (Gezira Journal of Health Sciences, 2014)
Objectives : To determine the prevalence and outcome of scorpion sting in Atbara and to give a brief  pathophysiology, clinical aspects, and management options. Methods : This is a retrospective study conducted at Atbara Teaching Hospital, Sudan, to look into the records of 428 scorpion envenomation  cases  in five years period from (2005-2009).  Results : Males constituted 51.2%, children below 15 were 37.2%, the overall death rate was 4.7% (n=20) and all of them were children. Most cases (88.4%) presented during the hot season. Conclusion : Scorpion sting is a life-threatening condition in children in Atbara, a better understanding of the condition and a proper management protocol may save lives.